Changes in yellow bristle grass (Setaria pumila) abundance after drought implications for pasture management - Tozer, K.N.; James, T.K.; Cameron, C.A. (New Zealand Plant Protection, 2009)
Yellow bristle grass (YBG) which is a summeractive annual grass reduces pasture quality and becomes unpalatable to stock as panicles mature Farmers are concerned that an extreme drought from November 2007 to March 2008 may have facilitated the spread of YBG and other summeractive annual grass weeds Botanical composition was assessed on 12 Waikato dairy farms in February 2009 and YBG abundance was related to key management factors These findings were compared with data collected from the same farms (February 2008) during the drought Between years ryegrass cover and the proportion of bare ground decreased These components were replaced by two summeractive annual grasses YBG and summer grass and to a lesser extent summeractive perennial grasses clovers and dicots In 2009 YBG cover was negatively associated with summeractive perennial grass cover and pH and positively associated with YBG cover in the previous summer and soil calcium levels